Predictive integrated numerical approach for modeling spatio-temporal microstructure evolutions and grain size dependent phase transformations in steels - Chen, Shuai-Feng; Bandyopadhyay, Kaushik; Basak, Shamik; Hwang, Byoungchul; Shim, Jae-Hyeok; Lee, Joonho; Lee, Myoung-Gyu (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
A computational modeling for predicting microstructure evolutions and mechanical properties of steels under thermo-mechanical-metallurgical process is established, for the first time, by integrating the finite element (FE) simulation, cellular automaton simulation (CA), and phase transformation kinetics. In this microstructural-integrated modeling, various recrystallization processes, such as dynamic recrystallization (DRX), meta-DRX, and static recrystallization (SRX), are formulated based on dislocation density based constitutive laws. With microstructure information provided by the CA modeling, the austenite grain size (AGS)-dependent phase kinetics in the form of continuous cooling transformation (CCT) diagram is applied for addressing the effect of AGS on transformations under various cooling conditions. The integrated numerical approach implemented in the FE software via user defined subroutines can simulate the morphology and size distribution of constituent grains, transformed fractions of various phases, hardness profiles and flow stresses after thermo-mechanical process with large plastic deformation. As a validation of the integrated modeling, the multiple oval-round pass hot rolling and subsequent cooling process are simulated for the seismic reinforcing steel bar and the predicted microstructure and mechanical properties are compared to those of experimental data.